2011
DOI: 10.1097/jgp.0b013e3181e4490d
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Slowing Associated With Elevated Serum Anticholinergic Activity in Older Individuals is Decreased by Caffeine Use

Abstract: Objectives The present study examined whether some of the age-associated decrements in basic cognitive resources (information-processing speed and working memory) result from anticholinergic medication use (as measured by serum anticholinergic activity) and whether such decrements are lessened by caffeine. Design Cross-sectional observational study Setting University medical center Participants 152 normal-elderly community volunteers Measurements Two tests each of information-processing speed and of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…From the aforementioned studies, majority examined (n = 24) an association between SAA and cognitive outcomes [ 7 , 8 , 10 13 , 40 – 50 , 52 54 , 56 , 57 , 60 , 61 ] using mostly MMSE as a standard measure of cognitive performance. Limited studies (n = 8) reported an association between SAA and both cognitive, and functional outcomes [ 14 , 16 18 , 55 , 57 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the aforementioned studies, majority examined (n = 24) an association between SAA and cognitive outcomes [ 7 , 8 , 10 13 , 40 – 50 , 52 54 , 56 , 57 , 60 , 61 ] using mostly MMSE as a standard measure of cognitive performance. Limited studies (n = 8) reported an association between SAA and both cognitive, and functional outcomes [ 14 , 16 18 , 55 , 57 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could help explain the lack of beneficial effect of estrogen therapy on cognitive performance in older women who have not used estrogen therapy for many years, such as in the very large and highly publicized Women’s Health Initiative Memory Study (Coker et al, 2010). Use of co-medications with significant anti-cholinergic activity also could significantly curtail the beneficial effects of estrogen therapy on cognitive performance and contribute to diminished effect in specific patient populations (Carriere et al, 2009; Nebes et al, 2010; Vinogradov et al, 2009). Collectively, these findings suggest that combining a cholinesterase inhibitor with E2 therapy may be most effective in recently postmenopausal women or women with early signs of mild cognitive impairment or AD, and least effective in women with advanced AD or who are on medications with significant anti-cholinergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Karachi et al recently wrote that “cholinergic neurons of the PPN play a central role in controlling gait and posture and represent a possible target for pharmacological treatment of gait disorders in PD” [115]. Another possibility is that the cholinergic changes reflect more general cognitive deficits and are not necessarily PPN-mediated; serum levels of cholinergic activity have also been related to reaction times and cognitive slowing [114,116]. …”
Section: Neuroimaging Evidence Linking Cognitive Function and Gaitmentioning
confidence: 99%